Kapasitas antioksidan, sitotoksisitas dan cemaran bakteri simplisia makroalga cokelat: Antioxidant capacity, cytotoxicity, and bacterial contamination of brown macroalgae simplicia - Permatasari, Anak Agung Ayu Putri; Wiradana, Putu Angga; Sari, Ni Kadek Yunita; Widhiantara, I Gede; Rosiana, I Wayan; Sandhika, I Made Gde Sudyadnyana; Sucipto, Teguh Hari; Panjaitan, Novaria Sari Dewi; Permatasari, Anak Agung Ayu Putri Permatasari (Jurnal Pengolahan Hasil Perikanan Indonesia, 2024)
Brown algae are considered to be a source of antioxidants that can contribute to improving health. The purpose of this study was to determine the best combination of brown algae and solvent types based on the parameters of antioxidant capacity, toxicity to Vero cells, and bacterial contamination that affects brown algae simplicia during 30 d of storage. Brown algae, Sargassum aquifolium and Padina australis, were collected from Sanur Beach at the lowest point in the intertidal zone. Extraction was performed using three solvents: ethanol, methanol, and distilled water. The antioxidant capacity of the brown algae extracts was measured using the DPPH method. The brown algae extract, which showed antioxidant capacity and IC50 in the strong category, was used for cytotoxicity testing. Bacterial contamination testing was performed based on the simple storage time of brown algae for 30 d. The results showed that the combination of S. aquifolium and P. australis ethanol extract (ratio 1:10) had a yield percentage of 37.2% with an antioxidant capacity of 0.935±0.003 mg/L GAEAC and an IC50 value of 89.03 μg/mL (strong category). The combination of S. aquifolium and P. australis ethanol extracts had an IC50 value of 382.30 μg/mL (the weak category). Total plate count (TPC), Enterobacteriaceae, and coliforms increased with the storage time of simplicia for 30 days. These findings indicate that the combination of ethanol extracts of S. aquifolium and P. australis is a potential source of natural antioxidants.